2018
DOI: 10.1128/jb.00425-18
|View full text |Cite
|
Sign up to set email alerts
|

Assembly Order of Flagellar Rod Subunits in Bacillus subtilis

Abstract: Bacterial flagella contain an axle-like rod that transits the cell envelope and connects the transmembrane basal body to the extracellular hook and filament. Although the rod is a crucial component of the flagellum, its structure and assembly are poorly understood. Previous reports defining the order of rod assembly in Gram-negative bacteria suggest that the rod requires five proteins to successfully assemble but assembly intermediates have not been well characterized due to metastablity and periplasmic proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…The supernatant was removed and centrifuged 100, 000 x g for 1 h to pellet membranes, and the resulting membranes were suspended in resuspension buffer. As previously described [38], the OD 600 of each membrane suspension was measured in a spectrophotometer (Genesys 10S UV-VIS spectrophotometer, Thermo Scientific) to allow equivalent amounts of membranes to be used for SDS-PAGE. Membranes were heated for 15 min at 95°C after the addition of 4 x SDS sample buffer (200 mM Tris-Cl [pH 6.8], 100 mM DTT, 8% SDS, 0.4% bromophenol blue, and 40% glycerol).…”
Section: Western Blotsmentioning
confidence: 99%
“…The supernatant was removed and centrifuged 100, 000 x g for 1 h to pellet membranes, and the resulting membranes were suspended in resuspension buffer. As previously described [38], the OD 600 of each membrane suspension was measured in a spectrophotometer (Genesys 10S UV-VIS spectrophotometer, Thermo Scientific) to allow equivalent amounts of membranes to be used for SDS-PAGE. Membranes were heated for 15 min at 95°C after the addition of 4 x SDS sample buffer (200 mM Tris-Cl [pH 6.8], 100 mM DTT, 8% SDS, 0.4% bromophenol blue, and 40% glycerol).…”
Section: Western Blotsmentioning
confidence: 99%
“…From these results, it was proposed that the order of assembly of the rod proteins in R. sphaeroides is FliE, FlgB, FlgF, FlgC and FlgG [91]. This order is different to the one proposed for the Gram-positive bacterium Bacillus subtilis and the spirochete Borrelia burgdorferi, where it was suggested that the rod proteins are assembled in the following order: FliE, FlgB, FlgC, FlhO (FlgF), and FlgG [40,92]. The difference between the order of assembly proposed for R. sphaeroides and B. subtilis or B. burgdorferi could be explained by the different experimental approaches used in these studies or possibly due to an actual difference between these organisms in the order of assembly of the rod structure.…”
Section: Rod Assembly and Opening Of The Peptidoglycan Barriermentioning
confidence: 80%
“…A failure to detect extracellular CwlQ could either indicate that CwlQ was not secreted and functioned in the cytoplasm, or that it was secreted and subsequently degraded by extracellular proteases as has been shown for other flagellar proteins in B. subtilis (16,58). To determine whether secreted proteases contributed to extracellular CwlQ degradation, pellets and TCA-precipitated supernatants were harvested, resolved, and subjected to Western blot analysis in a variety of strains deleted for seven extracellular proteases (∆7) (58).…”
Section: Resultsmentioning
confidence: 99%
“…The first architectural unit of the flagellum to be assembled is the basal body that is inserted in the plasma membrane and houses a dedicated type III secretion system (9,10). Once activated, the type III secretion system secretes the distal components of the flagellum including the structural units of the axle-like rod that is polymerized until it reaches the outer membrane in Gram-negative bacteria, followed by the flexible universal-joint hook (11)(12)(13)(14)(15)(16). Hook synthesis terminates when it reaches a particular length, at which point the secretion system transitions to exporting subunits that form the long helical polymer of the filament (17,18).…”
Section: Introductionmentioning
confidence: 99%